2018
DOI: 10.1002/14651858.cd003317.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for acute stroke

Abstract: GRADE Working Group grades of evidence. High quality: Further research is very unlikely to change our confidence in the estimate of effect. Moderate quality: Further research is likely to have an important impact on our confidence in the estimate of effect and may change the estimate. Low quality: Further research is very likely to have an important impact on our confidence in the estimate of effect and is likely to change the estimate. Very low quality: We are very uncertain about the estimate.a Of the 33 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…The included CSRs focused on 50 different diseases or conditions. Eight reviews (16%) evaluated acupuncture for joint and muscle pain [8,18,20,22,23,25,34,36], 5 reviews (9%) for obstetrics [11,16,41,42,44], 5 reviews (9%) for gynecological diseases [7,31,32,43,56], 3 reviews (4%) for stroke [51,52,54] and 2 reviews (4%) for smoking cessation [21,48] The other diseases are listed in Table S1.…”
Section: Treated Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included CSRs focused on 50 different diseases or conditions. Eight reviews (16%) evaluated acupuncture for joint and muscle pain [8,18,20,22,23,25,34,36], 5 reviews (9%) for obstetrics [11,16,41,42,44], 5 reviews (9%) for gynecological diseases [7,31,32,43,56], 3 reviews (4%) for stroke [51,52,54] and 2 reviews (4%) for smoking cessation [21,48] The other diseases are listed in Table S1.…”
Section: Treated Conditionsmentioning
confidence: 99%
“…The conclusions of included CSRs can be summarized into four categories: 1) thirty-two reviews (64%) concluded that the evidence was not sufficient or the level of evidence was not adequate; 2) seven reviews (14%) reported positive results and found acupuncture to be effective in the treatment of chronic kidney disease [26], induction of labor [42], episodic migraine [32], tension- type headache [33], fibromyalgia [18], pain in childbirth [41], and nausea and vomiting after surgery [30]; 3) ten reviews (20%) reported "potential efficacy" for acute management and rehabilitation of traumatic brain injury [49], endometrial pain [56], osteoarthritis [34], schizophrenia [39], post stroke rehabilitation [52] breech presentation [16], side effects of chemotherapy or radiotherapy in persons with cancer [55], acute stroke [51], induction of labour [44], premenstrual syndrome [7]; and 4) one review reported negative results for irritable bowel syndrome [35]. With regard to acupuncture safety, 24 reviews (48%) reported adverse events in the included RCTs, eleven reviews (22%) did not report information about adverse events [8, 20, 22, 32-34, 37, 41, 42, 48, 50], and 15 reviews (30%) reported no adverse events [7, 9, 11, 17, 18, 21, 26, 28, 29, 38-40, 43, 49, 56].…”
Section: Outcomes and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Engrafted alternating current stimulation by fine filiform needle, known as electroacupuncture (EA), is widely used clinically to treat brain disorders in Oriental medicine [ 13 ]. In addition, it is accepted as a common complementary therapy for the treatment of stroke [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Engrafted alternating current stimulation by fine filiform needle, known as electroacupuncture (EA), is widely used clinically to treat brain disorders in Oriental medicine [ 13 ]. In addition, it is accepted as a common complementary therapy for the treatment of stroke [ 13 , 14 ]. EA can ameliorate motor dysfunction and cognitive impairment in ischemic brain disorders by enhancing the proliferation and differentiation of neural stem cells [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%